Does level of minority presence and hospital reimbursement policy influence hospital referral region health rankings in the United States. (12th September 2018) - Hamadi, Hanadi; Apatu, Emma; Loh, Chung‐Ping Albert; Farah, Hyett; Walker, Kirk; Spaulding, Aaron
Summary: The shift from a fee‐for‐service payment to a value‐based payment scheme, sparked by the Patient Protection and Affordable Care Act, introduced pay‐for‐performance programs such Hospital Value Based Purchasing. Previous inquiry has not considered how local community factors may affect hospital system performance. This study investigated the association between local health performance and minority population in a hospital referral region (HRR). The primary objective was to ascertain whether community diversity levels are significantly associated to local health performance guided by the ecological model. Secondary data analysis collected from the 2016 American Hospital Association, Area Health Resource File, Commonwealth Fund Scorecard on Local Health System Performance, and the Dartmouth Atlas HRR dataset was used. Our primary findings show that the more diverse a HRR is, the more likely it is to be associated with lower ranking for access and affordability prevention and treatment avoidable hospital use and cost as well as healthy lives. Total performance score was significantly related to a better health ranking on prevention and treatment, hospital use, and cost, as well as healthy lives. This research supports the assertion that communities, particularly minorities in those communities, affect local health care performance in a variety of ways.